2019
DOI: 10.3847/1538-4357/ab48eb
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the O vi Circumgalactic Medium: Halo Mass Dependence and Outflow Signatures

Abstract: We probe the high-ionization circumgalactic medium by examining absorber kinematics, absorber-galaxy kinematics, and average absorption profiles of 31 O VI absorbers from the "Multiphase Galaxy Halos" Survey as a function of halo mass, redshift, inclination, and azimuthal angle. The galaxies are isolated at 0.12 < z gal < 0.66 and are probed by a background quasar within D ≈ 200 kpc. Each absorber-galaxy pair has Hubble Space Telescope images and COS quasar spectra, and most galaxy redshifts have been accurate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 93 publications
3
23
0
Order By: Relevance
“…Interestingly, they did not detect C in groups that include more than seven galaxies. It was also shown that O absorption within galaxy groups exhibits lower column densities and lower velocity spreads when compared to isolated environments (Stocke et al 2013;Pointon et al 2017;Ng et al 2019). This is consistent with cosmological simulations that show that since the virial temperature increases with halo mass, group environments ionize a larger fraction of oxygen to higher levels, which results in a lower ionization fraction of O compared to isolated galaxies (Oppenheimer et al 2016).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, they did not detect C in groups that include more than seven galaxies. It was also shown that O absorption within galaxy groups exhibits lower column densities and lower velocity spreads when compared to isolated environments (Stocke et al 2013;Pointon et al 2017;Ng et al 2019). This is consistent with cosmological simulations that show that since the virial temperature increases with halo mass, group environments ionize a larger fraction of oxygen to higher levels, which results in a lower ionization fraction of O compared to isolated galaxies (Oppenheimer et al 2016).…”
Section: Introductionsupporting
confidence: 79%
“…The O absorption is kinematically spread over Δ 90 = 419 km s −1 , which is among the four systems with the largest kinematic spreads at < 1 (M15, and references therein). Ng et al (2019) found that O absorption along the minor axis of edge- Oppenheimer et al (2016) and Ng et al (2019). Orange points are the simulated galaxies, larger solid blue diamonds represent the group environments, and the smaller open blue diamonds refer to isolated galaxies.…”
Section: Mid-to High-ionization Phasesmentioning
confidence: 99%
“…It is plausible that G1547 is low star-forming, green-valley galaxy that is becoming quenched due to a lack of CGM. massive systems have hot virial temperatures and there is little O to be found, since oxygen resides in even higher ionisation phases (Oppenheimer et al 2016;Ng et al 2019). Burchett et al (2016) found similar results for C , whereby the detection rate is lower for galaxies found in over-densities and/or residing in groups with dark matter halo masses of h > 10 12.5 M .…”
Section: Discussionmentioning
confidence: 68%
“…The only ion where upper limits are less common at low impact parameter is O as there are only 9 non-absorbing galaxies within 100 kpc. It has been noted that a lack of O could either be attributed to the lack of star formation Tumlinson et al (2011), or due to a halo mass and O column density dependence (Ng et al 2019;Oppenheimer et al 2016). We next explore additional measurable properties of G1547 with the goal of inferring why it lacks significant absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation